Beyond Pa Hill : a photographic synthesis of remembrance & construction : a thesis presented in partial fulfilment of the requirements for the degree of Master of Fine Arts at Massey University, Wellington, New Zealand - Stewart-MacDonald, Bonny; Stewart-MacDonald, Bonny (Massey University, 2011)
How can archival and constructed photographs be synthesised to make the sensual and spatial memories of home tangible? Drawing on phenomenological memories of a particular domestic space, the unification of varying photographic practices is examined for the purposes of achieving a synthesis of remembrance and construction, relative to the original home and within the context of the contemporary still life.
Keywords: Memories in photography; Still-life photography